Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examination June 1989: 1. Metals 2. Woods - Caribbean Examinations Council (CXC, 1989)
This report contains general and detailed comments on the performance of candidates in the June 1993 Caribbean Secondary Education Certificate Examinations (CSEC) in 1. Metals 2. Woods.
Keywords: CXC CSEC examinations